Community-Based Training for Pesantren Cadres in Producing Celery Extract Drinks to Support Hypertension Prevention - Abraham Ahmad Ali Firdaus; Paramita Sari; Mia Puspitasari; Ken Putri Raudhatul Jannah; Dewi Adila Sonia Zain; Alief Aditya Permana; Ghalief Fernanda Putra Fardian; Din Farhan Kamil; Mufidah Sheena (UKInstitute, 2026)
Non-communicable diseases are the leading cause of death globally, with hypertension being one of the most prevalent conditions characterized by elevated blood pressure above normal limits. In Sampang Regency, Madura, more than 15,000 hypertension cases were reported in 2022, reflecting significant public health concern. Poor health literacy, high-salt and high-fat dietary habits, and lack of physical activity contribute to the growing incidence. This community service program was conducted at Darussalam Al-Faisholiyah Islamic Boarding School in Sampang, aiming to improve the capacity of pesantren cadres in hypertension prevention through training on producing herbal drinks made from celery extract as a complementary therapy. The program included educational sessions on hypertension, hands-on practice in herbal drink preparation, and pre-test and post-test evaluations. Fifteen pesantren cadres actively participated in the activity. The results showed an increase in participants’ average knowledge scores from 7.4 to 8.4, indicating better understanding and practical skills. The program successfully enhanced health literacy, promoted healthy lifestyle awareness, and empowered the pesantren community to engage in preventive health practices. This initiative has the potential to be replicated in other pesantren to expand its preventive impact on hypertension, with continued mentoring and cadre monitoring recommended for sustainability.